2019
DOI: 10.1093/nar/gkz550
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for APOBEC3G catalytic exclusion of RNA and non-substrate DNA

Abstract: The potent antiretroviral protein APOBEC3G (A3G) specifically targets and deaminates deoxycytidine nucleotides, generating deoxyuridine, in single stranded DNA (ssDNA) intermediates produced during HIV replication. A non-catalytic domain in A3G binds strongly to RNA, an interaction crucial for recruitment of A3G to the virion; yet, A3G displays no deamination activity for cytidines in viral RNA. Here, we report NMR and molecular dynamics (MD) simulation analysis for interactions between A3Gctd and multiple sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 64 publications
5
14
0
Order By: Relevance
“…In the A3B-ACC 0 (U) complex, the side chain of active site residue Asn240 changed conformation, and hydrogen bond with the ssDNA backbone was lost. This conformer change is similar to what was previously observed for A3G nonsubstrate (rC) simulations ( 7 ), which suggests that cytidine was unstable and not poised for deamination. In conclusion, A3B can accommodate both DNA conformations but strongly prefers ATC 0 substrate.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In the A3B-ACC 0 (U) complex, the side chain of active site residue Asn240 changed conformation, and hydrogen bond with the ssDNA backbone was lost. This conformer change is similar to what was previously observed for A3G nonsubstrate (rC) simulations ( 7 ), which suggests that cytidine was unstable and not poised for deamination. In conclusion, A3B can accommodate both DNA conformations but strongly prefers ATC 0 substrate.…”
Section: Resultssupporting
confidence: 87%
“…The two-domain A3s consist of a catalytically active C-terminal domain (CTD) and an N-terminal domain (NTD) that binds to substrate but has no deamination activity. A3s deaminate cytosine to uracil on single-strand DNA (ssDNA) and certain RNAs ( 6 , 7 ), thus creating mutations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these observations, our EMSA data clearly demonstrate that residues in the loop 1 of A3C regulate protein-DNA interaction and we postulate that this interaction is causative for the enhanced deamination activity and enhanced anti-HIV and L1 activity. A similar model was discussed by Solomon and coworkers, which demonstrated that loop 1 residues of hA3G-CTD-2K3A-E259A (a catalytically inactive form of A3G-CTD) strongly interact with substrate ssDNA and that this distinguishes catalytic binding from non-catalytic binding [81]. Interestingly, loop 1 of A3A was found to be important for substrate specificity but not for substrate binding affinity [82], while loop 1 of A3H especially residue R26, plays a triple role for RNA binding, DNA substrate recognition, and catalytic activity likely by positioning the DNA substrate in the active site for effective catalysis [83].…”
Section: Discussionmentioning
confidence: 55%
“…We then incorporated this dZ monomer into a short DNA oligonucleotide (5′-AATCCdZAAA) using an AKTA Oligopilot10 at a 12 μmole synthesis scale in place of the target cytidine, in the preferred 5′-CCCA-binding motif for A3G. The oligonucleotide sequence used in this work matches that of our previous work 31,32 . Activated 2′-deoxy-zebularine generates strong affinity to catalytically active A3G-CTD We tested the binding affinity of the 9 nt dZ-oligonucleotide (DNA: 5′-AATCCdZAAA) and the catalytically active and soluble A3G-CTD variant (referred to throughout as A3G-CTD2) 31 , or the catalytically inactive A3G-CTD2 mutant (E259A mutation, referred to throughout as A3G-CTD2*).…”
Section: Synthesis Of Dz Phosphoramidite and Dz-containing Oligonucle...mentioning
confidence: 91%